PERBANDINGAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN TIPE TWO STAY TWO STRAY TERHADAP HASIL BELAJAR SISWA PADA MATERI ELASTISITAS - Anwar, Miftahul; Yuliani, Hadma; Fatmawati, Sri Fatmawati (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2018)
This study was aimed (1) is there any significant to improve students’ learning outcomes using cooperative model jigsaw and two stay two stray types, (2) is there any significant difference students’ learning outcomes using cooperative model jigsaw and two stay two stray types, (3) student and teacher activities using cooperative model jigsaw and two stay two stray types. This study was used quantitative approach which apllies comparative and descriptive research. The static group pretest-posttest design was used in this research. The sample was taken using judgment sampling, 5 of XI-IA and 6 of XI-IA students were used as sample. This study was conducted at MAN of Palangka Raya on September to October 2017. The student’s cognitive learning outcomes, afektif and psychomotoric observation students’ learning outcomes, and students and teacher activities were used as instruments. The result of this study obtained by (1) there is any a significance to improve students’ learning outcomes using cooperative model jigsaw and two stay two stray types, (2) there is nothing a significant difference students’ learning outcomes using cooperative model jigsaw and two stay two stray types, (3) the teacher activities using cooperative model using jigsaw type with a mean 82,89 high category and cooperative model using two stay two stray type with a mean 84, 20 high category, the students activities using cooperative model using jigsaw type with a mean 79,85 high category and cooperative model using two stay two stray type with mean 83,58 high category.